Downhill Speed Control of In-Wheel Motor During Regenerative Braking - Bayır, Raif; Soylu, Tuncay (Elektronika ir Elektrotechnika, 2017)
Recovering kinetic energy in an electric vehicle is important in order to use battery more effective and to extend the vehicle’s maximum distance range. In this study, regenerative braking is simulated and implemented on a test bed for a lightweight electric vehicle on the three different downhill that are 3º, 4º and 5º slopes at 30km/h conditions. An in-wheel motor which is generally used in the light electric vehicle is used for the regenerative braking application. Speed of the in-wheel motor is controlled with PID controller during regenerative braking. The in-wheel motor charges batteries and the PID controller maintain speed of the in-wheel motor to reference speed in both simulation study and experimental study. Graphics and outcomes of the simulation and experiment are showed in the results and discussion section. DOI: http://dx.doi.org/10.5755/j01.eie.23.6.19693